International trade makes European food markets less vulnerable to concurrent and recurrent climate extremes - Simone Pieralli; Ignacio Pérez-Domínguez (Environmental Research: Food Systems)
Extreme weather events are occurrences of unusually severe weather or climate conditions that can devastate local communities, agriculture and natural ecosystems. Due to climate change, these extreme events are becoming increasingly more likely, lasting longer, and more severe in impact. In this paper, we illustrate the potential effects of concurrent and recurrent extreme weather events on EU agricultural commodity markets and, in particular, on production and trade. A combination of concurrent and recurrent events is expected to have a negative and compounding effect on domestic food supply and trade, making EU agricultural markets less resilient. A set of scenarios based on record low yields show how EU production could be drastically affected compared to a business-as-usual situation. Market disruptions would be potentially larger for commodities in which the EU has a strong net exporter position, such as wheat. In the absence of extremes in non-EU regions, trade reveals as a key element in buffering the adverse impacts of extreme events in the EU.